Pembelajaran Mitigasi Bencana Gempa Bumi Anak TK Di Lereng Gunung Merapi Yogyakarta - Dwi Jayanti Kurnia Dewi (Universitas Darunnajah, 2024)
Indonesia is at the meeting point of three Eurasian tectonic plates, causing the potential for earthquake disasters. The results of volcanic and tectonic activity contribute to the potential danger of earthquakes. Children can become victims of earthquakes, but this can be minimized by providing earthquake disaster mitigation education. Mitigating earthquake disasters is one of the preventive efforts, carried out to make children better prepared to face earthquake disasters. This research aims to get an idea of the readiness of kindergarten children in facing earthquake disasters. This preparedness is based on the implementation of earthquake disaster mitigation activities carried out at schools in the Mount Merapi Yogyakarta area with a radius of 10 kilometers from the top of the mountain. This research method uses a survey method, involving a sample of 75 kindergarten teachers. The data collection technique uses a questionnaire distributed in the Even Semester of the 2022/2023 Academic Year. A questionnaire was given to kindergarten teachers to obtain quantitative data regarding the implementation of earthquake disaster mitigation learning. Survey results on disaster mitigation learning for children have not been carried out routinely, only 11% of kindergarten teachers schedule lessons on earthquake topics every month, 7% of kindergarten teachers schedule earthquake simulations every month, and teachers experience difficulties and confusion when designing and learning earthquake disaster mitigation that is suitable for kindergarten children. Disaster mitigation learning needs to be given to kindergarten-age children who live in earthquake-prone areas such as Yogyakarta, and there needs to be innovation in earthquake disaster mitigation learning so that teachers no longer experience difficulties and confusion when designing and carrying out appropriate earthquake disaster mitigation learning for kindergarten children